Potential Molecular Mechanisms of Recurrent and Progressive Meningiomas: A Review of the Latest Literature - Peng, Wenjie; Wu, Pei; Yuan, Minghao; Yuan, Bo; Zhu, Lian; Zhou, Jiesong; Li, Qian (Frontiers in Oncology, 2022)
Meningiomas, the most frequent primary intracranial tumors of the central nervous system in adults, originate from the meninges and meningeal spaces. Surgical resection and adjuvant radiation are considered the preferred treatment options. Although most meningiomas are benign and slow-growing, some patients suffer from tumor recurrence and disease progression, eventually resulting in poorer clinical outcomes, including malignant transformation and death. It is thus crucial to identify these “high-risk” tumors early; this requires an in-depth understanding of the molecular and genetic alterations, thereby providing a theoretical foundation for establishing personalized and precise treatment in the future. Here, we review the most up-to-date knowledge of the cellular biological alterations involved in the progression of meningiomas, including cell proliferation, degradation of the extracellular matrix and basement membranes, neo-angiogenesis, inhibition of apoptosis, and immunogenicity. Focused genetic alterations, including chromosomal abnormalities and DNA methylation patterns, are summarized and discussed in detail. A further understanding of cellular biological and genetic alterations will provide new prospects for the accurate screening and treatment of recurrent and progressive meningiomas.